Answer:
I don’t know
Step-by-step explanation:
36.3 because the digit in the hundredths place is not 5 or greater
Answer:
![Fx=\frac{5\pm\sqrt{25+24} }{6}](https://tex.z-dn.net/?f=Fx%3D%5Cfrac%7B5%5Cpm%5Csqrt%7B25%2B24%7D%20%7D%7B6%7D)
Step-by-step explanation:
A quadratic equation in one variable given by the general expression:
![ax^2+bx+c](https://tex.z-dn.net/?f=ax%5E2%2Bbx%2Bc)
Where:
![a\neq 0](https://tex.z-dn.net/?f=a%5Cneq%200)
The roots of this equation can be found using the quadratic formula, which is given by:
![x=\frac{-b\pm\sqrt{b^2-4ac} }{2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%5Cpm%5Csqrt%7Bb%5E2-4ac%7D%20%7D%7B2a%7D)
So:
![y(x)=3x^2-5x-2=0](https://tex.z-dn.net/?f=y%28x%29%3D3x%5E2-5x-2%3D0)
As you can see, in this case:
![a=3\\b=-5\\c=-2](https://tex.z-dn.net/?f=a%3D3%5C%5Cb%3D-5%5C%5Cc%3D-2)
Using the quadratic formula:
![x=\frac{-b\pm\sqrt{b^2-4ac} }{2a}=\frac{-(-5)\pm\sqrt{(-5)^2-4(3)(-2)} }{2(3)}=\frac{5\pm\sqrt{25+24} }{6}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%5Cpm%5Csqrt%7Bb%5E2-4ac%7D%20%7D%7B2a%7D%3D%5Cfrac%7B-%28-5%29%5Cpm%5Csqrt%7B%28-5%29%5E2-4%283%29%28-2%29%7D%20%7D%7B2%283%29%7D%3D%5Cfrac%7B5%5Cpm%5Csqrt%7B25%2B24%7D%20%7D%7B6%7D)
Therefore, the answer is:
![Fx=\frac{5\pm\sqrt{25+24} }{6}](https://tex.z-dn.net/?f=Fx%3D%5Cfrac%7B5%5Cpm%5Csqrt%7B25%2B24%7D%20%7D%7B6%7D)
Answer:
1
Step-by-step explanation:
When we substract 1 from any number then will get just previous number.
Example :
Let any number 17
17-1 =16
16 is the just previous number of 17
Therefore, A number -1 = previous number
Answer will be 1